2012
DOI: 10.3341/kjo.2012.26.6.438
|View full text |Cite
|
Sign up to set email alerts
|

Astigmatic Changes after Horizontal Rectus Muscle Surgery in Intermittent Exotropia

Abstract: PurposeTo evaluate the changes of refractive astigmatism after horizontal rectus muscle surgery in intermittent exotropic children.MethodsSixty-nine exotropic patients were retrospectively reviewed. Of those, 35 patients received unilateral lateral rectus recession (BLR group, 35 eyes) and 34 patients received unilateral lateral rectus recession and medial rectus resection (R&R group, 34 eyes). Non-cycloplegic refractions were measured until 6 months postoperatively. Spherical equivalent (SE), J0 and J45 using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 20 publications
(48 reference statements)
7
36
1
3
Order By: Relevance
“…described by Hong and Kang [13] increased through the first 3 months of follow-up, and remained stable through postoperative month 6. Preslan et al [4] found that there was still a significant change in WTR astigmatism when patients were re-evaluated 4 months postoperatively, with 11% maintaining at least 1.0 D of astigmatic change and 38% maintaining at least 0.5 D of astigmatic change.…”
Section: Key Pointsmentioning
confidence: 83%
See 4 more Smart Citations
“…described by Hong and Kang [13] increased through the first 3 months of follow-up, and remained stable through postoperative month 6. Preslan et al [4] found that there was still a significant change in WTR astigmatism when patients were re-evaluated 4 months postoperatively, with 11% maintaining at least 1.0 D of astigmatic change and 38% maintaining at least 0.5 D of astigmatic change.…”
Section: Key Pointsmentioning
confidence: 83%
“…Studies by both Kwitko et al [6] and Bagheri et al [10] showed a myopic shift that was not statistically significant, whereas others found an initial trend toward myopia that was not sustained when followed for periods of 3-12 months [11 & ,12]. Some research described sustained myopia; Hong and Kang [13] showed a statistically significant myopic shift 6 months postoperatively, with a mean change in spherical equivalent of À0.66 AE 0.84 D after bilateral lateral rectus (BLR) recession and À0.25 AE 1.02 D after recession-resection. This persistent myopic shift was supported by Al-Tamimi et al [14 & ], who showed a mean change in spherical equivalent of 0.14 AE 0.85 D (P ¼ 0.18) 6 months postoperatively.…”
Section: Changes In Spherical Equivalentmentioning
confidence: 93%
See 3 more Smart Citations